Considering middle-classes in Latin America: An update of old debates - Díaz, Isabel (2022)
The approaches to the middle classes that have been dominant in Latin American thought and that structure current academic debate form the analytical nucleus of this article. In particular, this article focuses on stratification and social and political mobility, as topics of contemporary reflection, and the need to overcome myths that result from the unrestrained use of this concept. Following the optimism characteristic of the first two decades of the 21st century, questions emerge regarding the vulnerability of these middle segments of the population in the region. To synthesize these debates, this article offers a revision of the existing literature on the Latin American middle classes. The relationship between such classes and the state in the historical development of both in Latin America has been of central concern. In addition, certain myths are problematized that guide the public debate regarding the politicization of these sectors: neither “florindos” (self-centered) nor “ciudadanos de bien” (good citizens). Finally, the article reflects on how to study the middle layers of society in troubled times, placing labor uncertainty at the forefront of academic discussion.